Scandinavian journal of work and organizational psychology - Stockholms universitet; Forte, Forskningsrådet för hälsa, arbetsliv och välfärd (Sweden) (Stockholm University Press, 2016)
The aim of the Scandinavian Journal of Work and Organizational Psychology is to contribute to a better working life based on high-quality research. The journal seeks to publish papers covering the important issues in working life on all levels, including the societal, the organizational and the individual level. The journal also encourages research combining two or more of these levels and we invite empirical as well as theoretical, methodological and review manuscripts.
Keywords: Psychology, Industrial : Periodicals; Organizational behavior : Periodicals; Personnel management : Periodicals; Work : Psychological aspects : Periodicals; Organizational behavior; Personnel management; Psychology, Industrial; Work : Psychological aspects; Marketing & Sales